Strength Evaluation of Combined New and Old Plates Welded Joint: Case of Anggada XV Tug Boat - Nurcholik, Samsu Dlukha; Wahyuda, Wahyuda; Hidayat, Taufik; Arifuddin, Andi Mursid Nugraha; Kurniawati, Diniar Mungil; Saadiyah, Devy Setiorini; Awali , Jatmoko; Rohimsyah, Fikan Mubarok; Trimulyono, Andi; Kusuma, Andhi Indira (Indonesian Journal of Maritime Technology, 2024)
Naval grade plate is designed for shipbuilding due to its strength. In the shipyard, old plates have been used because surplusage of the previous project. However, the mechanical properties of old plate compared to new plate have not been clarified yet. In this study, a comparative investigation shielded metal arc welding (SMAW) of old plate and new plate was performed. A spectroscopy test was used to obtain the chemical properties of the old plate and the new plate. Furthermore, tensile and hardness tests were performed to investigate the mechanical properties It was concluded that (1) the chemical properties of the old and new plates are almost similar and (2) the average value of tensile strength of the old-old plate, new-new plate, and new-old plate are 451.3, 487, 454,3 N/mm2, respectively. (3) then, the average hardness test of HAZ of old plate, new plate, and weld metal are 73.2, 78.3, 83.2 HRB, respectively. From the results, it can be concluded that using old plates for shipbuilding is still reliable.